Immune infiltration analysis reveals immune cell signatures in salivary gland tissue of primary Sjögren’s syndrome - Gong, Hongxiao; Qiu, Xiaoting; Li, Pingping; Zhao, Runzhi; Wang, Beijia; Zhu, Ling; Huo, Xingxing (Frontiers in Medicine, 2023)
Mouse models are the basis for primary Sjögren's syndrome research, but the depth of comparison between mouse and human salivary gland immune cells is limited. Methods: First, gene expression profiles of salivary glands in normal and pSS patients were downloaded from the Gene Expression Omnibus database. The proportion of infiltrating immune cell subsets was then assessed by cell type identification by estimating relative subsets of RNA transcripts (CIBERSORT). The experimental Sjögren's syndrome (ESS) model mice were successfully constructed using salivary gland (SG) protein, and the successful model mice were screened. Based on the RNA-Seq data of mouse salivary gland tissue, the seq-ImmuCC model was used to quantitatively analyze the composition ratio of 10 immune cells in the salivary gland tissue of primary Sjögren's syndrome patients and mouse models. Results: In the study, 31 human data samples were calculated and finally obtained by the CIBERSORT deconvolution method. The results of immune cell infiltration showed that compared with normal human salivary gland tissue, the γδT cells were significantly different, and the content of naive CD4+ T cells was significantly increased, while the content of plasma cells was decreased. Principal component analysis (PCA) indicated differences in immune cell infiltration between pSS patients and normal subjects. Meanwhile, ESS model mice were constructed. The comprehensive analysis found that the proportion of monocytes in the salivary gland tissue of pSS patients and model mice decreased, while the proportion of macrophages increased. There were also some differences in the proportion of T cell and B cell infiltration. Through a comprehensive analysis of immune infiltration in the salivary glands of primary Sjögren's syndrome patients and model mice, we demonstrate the conservation and non-conservation of mouse and human immune systems at the immune cell level, helping to explain immune mechanisms during development. Primary regulation in Sjögren's syndrome.